Outcomes of Transzygomatic Middle Cranial Fossa Approach for Skull Base Tumors—A Single Institutional Experience - Manzoor, Nauman F.; Morone, Peter; Kelly, Patrick D.; Chotai, Silky; Yawn, Robert J.; Chambless, Lola B.; Thompson, Reid C.; Rivas, Alejandro (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective This study aimed to evaluate surgical outcomes after transzygomatic middle cranial fossa (MCF) (TZ-MCF) approach for tumor control in patients with large skull base lesions involving the MCF and adjacent sites.Setting This study was done at the tertiary skull base center.Design This is a retrospective case series.Main Outcome Measures The main outcome measures were tumor control (recurrence), new-onset cranial neuropathies, facial nerve and audiometric outcomes, cerebrospinal fluid (CSF) leak, and wound complications.Results Sixteen patients were identified with a median age of 45 years (range: 20–72). The mean maximum tumor dimension was 5.49 cm (standard deviation [SD]: 1.2, range: 3.1–7.3) and the mean tumor volume was 28.5 cm3 (SD: 18.8, range: 2.9–63.8). Ten (62.5%) tumors were left sided. The most common pathology encountered was meningioma (n = 7) followed by chondrosarcoma (n = 4). Mean follow-up was 36.3 (SD: 26.9) months. Gross total resection or near total resection was achieved in nine (56.2%) and planned subtotal resection was used in seven (43.7%). Postoperative additional new cranial nerve (CN) deficits included CN V (n = 1), CN III (n = 2), CN VI (n = 1), and CN X (n = 1). Major neurological morbidity (hemiplegia) was encountered in two patients with resolution. There were no cases of CSF leak, meningitis, hemorrhage, seizures, aphasia, or death. There was no recurrence or regrowth of residual tumor. Facial nerve function was preserved in all but one patient (House–Brackmann grade 2).Conclusion Various skull base tumors involving MCF with extension to adjacent sites can be successfully resected using the TZ-MCF approach in a multidisciplinary fashion. This approach yields optimal exposure and permits excellent tumor control with acceptable CN and neurological morbidity.
Keywords: extended middle cranial fossa; meningioma; schwannoma; chondrosarcoma; facial nerve